Regulating the Use of Artificially Intelligent Driving Algorithms Within the Artificial Intelligence & Internet of Things (AIoT) - Li, Lei; Wang, Chuyun (International Journal of Computer Science and Information Technology, 2025)
The advancement of the underlying technology and hardware devices of the Internet of Things (IoT) has led to the emergence of several new applications that are influencing the progress of human society in the era of the Artificial Intelligence IoT (AIoT). The application of AIoT has not only revolutionized the efficiency of human social life but also brought about moral and ethical hazards as well as legal issues. At a technological level, the algorithmic mechanism of AI driving is more complex than typical machine learning and requires regulation because to its automated decision-making process. The design of algorithmic regulation for AI driving should prioritize system safety, continuous improvement of regulation technology, implementation of algorithmic audit mode, and enhancement of overall efficiency in regulating algorithms.